Do Butterflies Bite? : Fascinating Answers to Questions about Butterflies and Moths - Davies, Hazel, 1968-; Butler, Carol A., 1943- (Book collections on Project MUSE., 2008)
How fast do butterflies fly? Does a butterfly have ears? Do they sleep? Does a caterpillar have a skeleton? How does a moth get out of its cocoon? What is the difference between a butterfly and a moth? And just what is a skipper? Every year, thousands of people visit butterfly conservatories to stand in quiet awe of the simple beauty displayed by these magical creatures. Hazel Davies and Carol A. Butler capture the sense of wonderment and curiosity experienced by adults and children alike in this book about butterflies and their taxonomic cousins, the moths and the skippers. Beautifully illustrated with color and black and white photographs, and drawings by renowned artist William Howe, this book is an essential resource for parents, teachers, students, or anyone who has ever been entranced by these fascinating, fluttering creatures. Covering everything from their basic biology to their complex behaviors at every stage of life to issues in butterfly conservation, Davies and Butler explore wide-ranging topics and supply a trove of intriguing facts. You'll find tips on how to attract more butterflies to your garden, how to photograph them, and even how to raise them in your own home. Arranged in a question and answer format, the book provides detailed information written in an accessible style that brings to life the science and natural history of these insects. In addition, sidebars throughout the book detail an assortment of butterfly trivia, while extensive appendices direct you to organizations, web sites, and more than 200 indoor and outdoor public exhibits, where you can learn more or connect with other lepidopterophiles (butterfly lovers).